PRINCIPLES OF JUSTICE IN ETHICS FROM NURCHOLISH MADJID'S PERSPECTIVE - Karim, Hafis Abdillah (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2024)
This research discusses the principles of justice in the ethical perspective of Nurcholish Madjid. A contemporary Muslim philosopher who is famous for his progressive and liberal thinking. The main focus of the research is to understand how the concept of ethics according to Nurcholish Madjid, the principles of justice in the perspective of Islamic ethics that he advocates, integrates the values of justice in Nurcholish Madjid's thinking and how they are implemented in contemporary society. This research aims to identify and analyze the way the concept of justice is carried out by each individual. The justice that Nurcholish Madjid means is something that has urgency regarding humanity, equality and ending injustice. The concept of ethics according to Nurcholish Madjid's views will be studied in the context of his philosophical thought which includes the principles of justice, economics,and social relations. The method used involves a philosophical analysis approach by exploring the main works of Nurcholish Madjid and relating them to the complex situations faced by individuals with contemporary moral challenges. This research uses qualitative methods through library research and descriptive analysis with literature relevant to Nucholish Madjid's thoughts. It is hoped that the results of this research will provide new insight into how the principles of justice in Nurcholish Madjid's ethical perspective can be applied in everyday life. Thus, this research attempts to deepen the understanding of the principles of justice in ethics based on the thoughts of Nurcholish Madjid.